A Prospective Clinical Study Characterizing the Influence of Morbid Obesity on the Pharmacokinetics of Gentamicin: Towards Individualized Dosing in Obese Patients - Smit, Cornelis; Wasmann, Roeland E.; Goulooze, Sebastiaan C.; Hazebroek, Eric J.; Van Dongen, Eric P. A.; Burgers, Desiree M. T.; Mouton, Johan W.; Brüggemann, Roger J. M.; Knibbe, Catherijne A. J. (Clinical pharmacokinetics, 2019)
Background and Objective Gentamicin is an aminoglycoside antibiotic predominantly used in bloodstream infections. Although the prevalence of obesity is increasing dramatically, there is no consensus on how to adjust the dose in obese individuals. In this prospective clinical study, we study the pharmacokinetics of gentamicin in morbidly obese and non-obese individuals to develop a dosing algorithm that results in adequate drug exposure across body weights. Methods Morbidly obese subjects undergoing bariatric surgery and non-obese healthy volunteers received one intravenous dose of gentamicin (obese: 5 mg/kg based on lean body weight, non-obese: 5 mg/kg based on total body weight [TBW]) with subsequent 24-h sampling. All individuals had a normal renal function. Statistical analysis, modelling and Monte Carlo simulations were performed using R version 3.4.4 and NONMEM ® version 7.3. Results A two-compartment model best described the data. TBW was the best predictor for both clearance [CL = 0.089 × (TBW/70) 0.73 ] and central volume of distribution [ V c = 11.9 × (TBW/70) 1.25 ] (both p < 0.001). Simulations showed how gentamicin exposure changes across the weight range with currently used dosing algorithms and illustrated that using a nomogram based on a ‘dose weight’ [70 × (TBW/70) 0.73 ] will lead to similar exposure across the entire population. Conclusions In this study in morbidly obese and non-obese individuals ranging from 53 to 221 kg we identified body weight as an important determinant for both gentamicin CL and V c . Using a body weight-based dosing algorithm, optimized exposure across the entire population can be achieved, thereby potentially improving efficacy and safety of gentamicin in the obese and morbidly obese population. Trial Registration Registered in the Dutch Trial Registry (NTR6058).